RF MEMS based tunable bowtie shaped substrate integrated waveguide filter - Rehman, M.Z.U. (Czech Technical University, 2015)
A tunable bandpass filter based on a technique that utilizes substrate integrated waveguide (SIW) and double coupling is presented. The SIW based bandpass filter is implemented using a bowtie shaped resonator structure. The bowtie shaped filter exhibits similar performance as found in rectangular and circular shaped SIW based bandpass filters. This concept reduces the circuit footprint of SIW; along with miniaturization high quality factor is maintained by the structure. The design methodology for single-pole triangular resonator structure is presented. Two different inter-resonator couplings of the resonators are incorporated in the design of the two-pole bowtie shaped SIW bandpass filter, and switching between the two couplings using a packaged RF MEMS switch delivers the tunable filter. A tuning of 1 GHz is achieved for two frequency states of 6.3 and 7.3 GHz. The total size of the circuit is 70 mm Ã 36 mm Ã 0.787 mm (L Ã W Ã H).